Protonophore treatment augments energy expenditure in mice housed at thermoneutrality - Sadler, Daniel G.; Landes, Reid D.; Treas, Lillie; Sikes, James; Porter, Craig (Frontiers in Physiology, 2024)
Background: Sub-thermoneutral housing increases facultative thermogenesis in mice, which may mask the pre-clinical efficacy of anti-obesity strategies that target energy expenditure (EE). Here, we quantified the impact of protonophore treatment on wholebody energetics in mice housed at 30°C. Methods: C57BL/6J mice (n=48, 24M/24F) were housed at 24°C for two weeks; 32 (16M/16F) were then transitioned to 30°C for a further four weeks. Following two weeks acclimation at 30°C, mice (n=16 per group, 8M/8F) received either normal (0 mg/L; Control) or supplemented (400 mg/L; 2,4-Dinitrophenol [DNP]) drinking water. Mice were singly housed in metabolic cages to determine total EE (TEE) and its components via respiratory gas exchange. Mitochondrial respiratory function of permeabilized liver tissue was determined by high-resolution respirometry. Results: Transitioning mice from 24°C to 30°C reduced TEE and basal EE (BEE) by 16% and 41%, respectively (both P<0.001). Compared to 30°C controls, TEE was 2.6 kcal/day greater in DNP-treated mice (95% CI: 1.6 to 3.6 kcal/day, P<0.001), which was partly due to a 1.2 kcal/day higher BEE in DNP-treated mice (95% CI: 0.6 to 1.7 kcal/day, P<0.001). The absolute TEE of 30°C DNP-treated mice was lower than that of mice housed at 24°C in the absence of DNP (DNP: 9.4±0.7 kcal/day vs. 24°C control: 10.4±1.5 kcal/day). DNP treatment reduced overall body fat of females by 2.9 percentage points versus sexmatched controls (95% CI: 1.3 to 4.5 %, P<0.001), which was at least partly due to a reduction in inguinal white fat mass. Conclusion: Protonophore treatment markedly increases EE in mice housed at 30°C. The magnitude of change in TEE of mice receiving protonophore treatment at 30°C was smaller than that brought about by transitioning mice from 24°C to 30°C, emphasizing that housing temperature must be considered when assessing anti-obesity strategies that target EE in mice.